Evaluation of the RESIST-4 O.K.N.V immunochromatographic lateral flow assay for the rapid detection of OXA-48, KPC, NDM and VIM carbapenemases from cultured isolates. Issue 5 (1st July 2019) - MacDonald, James Wesley; Chibabhai, Vindana
Abstract : Purpose This study aimed to evaluate the performance of the RESIST-4 O.K.N.V immunochromatographic lateral flow assay for the detection of OXA-48, KPC, NDM and VIM carbapenemases in 100 clinical Enterobacteriaceae isolates using solid culture media. Methodology In total, 100 clinical Enterobacteriaceae isolates with characterized β -lactamase enzymes (OXA-48 n =46, KPC n =4, NDM n =43 and VIM n =10) were evaluated using the RESIST-4 O.K.N.V assay. The assay was also evaluated using carbapenem-sensitive control strains and confirmed non-carbapenemase-producing Enterobacteriaceae clinical isolates resistant to carbapenems. Inter-rater agreement of the test was evaluated by four different users who tested 11 randomly selected isolates daily over 3 days. Results Overall accuracy of the assay was 99.5  %. For the detection of KPC, OXA-48 and its variants and VIM the assay correctly identified 100  % of the isolates when compared to PCR. Initial performance for NDM detection was sensitivity=95.3 %, specificity=100  %. Two PCR positive Providencia rettgeri isolates rendered false negative results on the assay. Retesting from a carbapenem zone of inhibition rendered a positive result for both isolates increasing the sensitivity to 100  %. No false positive results or cross reactions were detected. Conclusion The RESIST-4 O.K.N.V is reliable, sensitive and specific for the detection of OXA-48, KPC, NDM and VIM carbapenemases. Further evaluation on improving NDM detection in organisms from the Proteeae tribe is warranted to determine optimal test conditions.